(untitled) (Pakistan Journal of Science, 2022)
Pulp and paper industrial effluent has the foremost role in environmental pollution. The key factor of the current study is to determine the conjugative effect of charcoal (60%) and alluvial soil (40%) mixture with laccase enzyme to lessen the effluent load of the pulp and paper industry. The adsorbent mixture of charcoal (60%) and alluvial soil (40%) was used for the adsorption of biological oxygen demand (BOD) chemical oxygen demand (COD), color, and lignin of effluent. The impact of pH, temperature, adsorbent concentration, and adsorption time on the removal procedure were studied. Adsorption equilibrium was achieved after 50 minutes with an agitation rate of 500 rpm at pH 6.0 at 25 degree. Results indicated that COD, BOD, color, and lignin were removed 86%, 80%, 60%, and 62% respectively. Moreover, the laccase enzyme also enhanced the reduction of these parameters as COD 95%, BOD 93% color 83%, and lignin 75%. The experimental batch equilibrium adsorption for COD and BOD was analyzed by Freundlich and Langmuir models and kinetics was also discussed by pseudo-first-order and pseudo-second-order. The BOD and COD data fitted to the pseudo-secondorder kinetic model. Thermodynamics parameters ∆G˚, ∆H˚, and ∆S˚ results indicated that adsorption was nonspontaneous due to high TDS and lignin, endothermic in nature, and revealed an increase in randomness and degree of disorderliness at adsorbent mixture during the present study. Consequently, the use of laccase enzyme in combination with an adsorbent mixture presents promising results and is applicable.